Supplementation with yak (Bos grunniens) bone collagen hydrolysate altered the structure of gut microbiota and elevated short-chain fatty acid production in mice - Zitao Guo; Dalong Yi; Bo Hu; Lingyu Zhu; Ji Zhang; Yuliang Yang; Chunyu Liu; Yi Shi; Zhenghua Gu; Yu Xin; Huaigao Liu; Liang Zhang (Food Science and Human Wellness)
In this study, yak bone collagen hydrolysate (YBCH) was produced by mixed proteases and provided to standard-diet mice at a different dose (low dose (LD), medium dose (MD), and high dose (HD)) to investigate its effects on the composition of gut microbiota and short-chain fatty acids (SCFA) production. It was found that YBCH was mainly composed of small molecular peptides whose molecular weight below 2000 Da. Notably, supplementation with different doses of YBCH could significantly downregulate the ratio of Firmicutes to Bacteroidetes in the fecal microbiota. At the family level, the Lachnospiraceae abundance was significantly reduced in the YBCH gavage groups (mean reduction ratio 41.7 %, 35.2 %, and 36.4 % for LD, MD, and HD group, respectively). The predicted functions of gut microbes in the MD group were significantly increased at “lipid metabolism” and “glycan biosynthesis and metabolism”. Moreover, the SCFA production in the YBCH groups was elevated. Especially, the concentration of acetic acid, propionic acid, and butyric acid in the MD group was separately increased 79.7 %, 89.2 %, and 78.8 % than that in the NC group. These results indicated that YBCH might be applied in the development of functional food for intestinal microecological regulation.